Proteomic approaches to the study of renal mitochondria - Tuma, Zdenek; Kuncova, Jitka; Mares, Jan; Grundmanova, Martina; Matejovic, Martin (Biomedical papers, 2016)
Background and Aims: Dysfunction of kidney mitochondria plays a critical role in the pathogenesis of a number of renal diseases. Proteomics represents an untargeted attempt to reveal the remodeling of mitochondrial proteins during disease. Combination of separation methods and mass spectrometry allows identification and quantitative analysis of mitochondrial proteins including protein complexes. The aim of this review is to summarize the methods and applications of proteomics to renal mitochondria.Methods: Using keywords ``mitochondria'', ``kidney'', ``proteomics'', scientific databases (PubMed and Web of knowledge) were searched from 2000 to August 2015 for articles describing methods and applications of proteomics to analysis of mitochondrial proteins in kidney. Included were publications on mitochondrial proteins in kidneys of humans and animal model in health and disease.Results and Conclusion: Proteomics of renal mitochondria has been/is mostly used in diabetes, hypertension, acidosis, nephrotoxicity and renal cancer. Integration of proteomics with other methods for examining protein activity is promising for insight into the role of renal mitochondria in pathological states. Several challenges were identified: selection of appropriate model organism, sensitivity of analytical methods and analysis of mitochondrial proteome in different renal zones/biopsies in the course of various kidney disorders.
Keywords: renal mitochondria; proteomics; gel electrophoresis; liquid chromatography-mass spectrometry; diabetes; acidosis; nephrotoxicity; renal cancer